Developing Rahmatan lil 'Alamin-Based Islamic Religious Education in Indonesian Higher Education - Setiawan, Rahmadi Agus (Unisia, 2025)
This article examines approaches for advancing Islamic Religious Education (IRE) in higher education, centered on the principle of rahmatan lil 'alamin (mercy to all creation). It underscores the critical role of embedding values such as moderation, tolerance, social justice, and compassion within a curricular framework. Employing a qualitative literature review methodology, the study elucidates the foundational tenets of rahmatan lil 'alamin, identifies systemic barriers to its application, and advances actionable approaches for its pedagogical integration. Findings reveal that systematically incorporating these values into IRE can foster inclusive, moderate, and globally conscious students. Nevertheless, persisting challenges impede progress, including institutional resistance to curricular reform, educators’ limited grasp of the concept’s nuances, and sociopolitical pressures shaping policy. To mitigate these issues, the article recommends modernizing curricula to align with evolving societal demands, enhancing educators’ pedagogical capacities through targeted professional development, and fortifying institutional frameworks to reinforce value-based education. By pursuing these approaches, Islamic education can address contemporary global challenges and nurture a generation dedicated to peace and universal welfare, thereby enriching academic discourse on reimagining religious education for the modern era.